Antimicrobial activity and antibiotic modulating effect of the bark extract of Dahlstedtia araripensis (Benth) Fabaceae (Research, Society and Development, 2022)
There is a recurring concern about the increase in infections caused by fungi and bacteria in the hospital environment. Considering the increase in resistant microorganisms and with that the need for more aggressive treatments for the treatment of these infections, research with natural products has been an effective alternative in the search for new bioactive substances that fight different species of microorganisms. therefore, the preliminary studies with plant extracts are the basis for further work in this area. Dahlstedtia araripensis Benth (Fabaceae), popularly known as "angelim", is an endemic species from northeastern Brazil, with little research developed. This study aims to trace the preliminary chemical profile and evaluate the antimicrobial and antibiotic modulatory activity of the bark extract of the species D. araripensis (Benth). The secondary metabolite classes were identified from qualitative chemical prospecting. For the antimicrobial assays, 7 standard bacterial strains and 1 multidrug-resistant, and 3 fungal strains belonging to the genus Candida were used. Using the microdilution method the MIC for each strain was determined and the modulating potential of extract was evaluated. The chemical tests identified the presence of tannins and flavonoids. The antimicrobial assays showed good results against the Gram-Positive bacteria Streptococcus mutans and Enterococcus faecalis with MIC of 256 μg/mL, and a potentiation of the extract in the antibiotic benzylpenicillin action against E. faecalis. The extract did not show antifungal activity. Other works are essential for chemical characterization and bactericidal analysis by other more specific methods.